The application of drama in an institutional video of PCPD and UP Mindanao on Solid Waste Management for school children and educators in Davao City - Billano, Jessa Loreta C.
This video production thesis was conducted to create an institutional video about Solid Waste Management for schoolchildren and educators in Davao City. It was guided by the concepts of the Drama Theory and the Convergence Theory of Communication and made use of the application of the dramatic format of an institutional video. It defined drama as the portrayal of real and imagined events through acting with emphasis on conflict, tension and crisis. For this production thesis, drama was best portrayed by building conflict, struggle and crisis within the characters and their environment. The characters that were developed were based on the demographics and psychographics of the target audience in order to achieve identification, confrontation and behavioral change. Local disasters caused by wastes were also used to intensify drama in the video. Including basic information about SWM also worked for this video production since it was able to present the most fundamental yet crucial methods in waste management. Through this strategy, this institutional video is perceived to attract the audiences' attention with the characters and be confronted with their present negative actions towards their wastes therefore achieving a positive attitude change among them. Accordingly, this study is a contribution to the Philippine Center for Population and Development (PCPD) and University of the Philippines Mindanao's (UPMin) advocacy on ecological solid waste management to address the present and emerging perennial problems of our environment.